Recep????o e aplica????o da Lei Federal n?? 10.639/2003: da publica????o a pr??tica - Lima, Denise Maria Soares (2012)
Brazil is a country marred by inequalities, the result of racism, racial prejudice and discrimination. It is necessary to reflect about the conditions to create a culture that promotes human rights and values the Brazilian black population. In this sense, this research highlights public policy and education management, specifically aimed at the youth. It also objectives at verifying the reception and application of the Federal Law n. 10.639, of January 9, 2003, which amended the Guidelines and Bases of National Education Law, forcing public and private schools to teach History and Afro- Brazilian culture. Therefore the research conducted a survey in the local public schools to examine how secondary school teachers received the Law and how they apply their content, since its publication. Specifically, we sought to examine knowledge about the Law, the importance given by the teachers to racial ethnic education and observe how race relations work at the school. This is a qualitative-quantitative research, performed by semi structured interviews and questionnaires. For data analysis and discussion, we adopted context analysis along the lines suggested by Bardin (2009). The results achieved by this research indicate that the teachers of Distrito Federal know the Law, as well as consider it an important element in combating racism and racial prejudice present in schools. Moreover, teachers observe that the school disregard human rights and human dignity. However, a set of data suggests contradictory positions between the willingness to do and the difficulty to operationalize, mainly the non-applicability in a categorical way as it should expected from a legal device. Among the ways to enforce the actual Law, one of the most outstanding was the sporadic one and sometimes uncommitted approach, and in some cases, the enhancement of the inequalities without combating discrimination. In addition, the research showed another contradiction, the recognition of the Law as a mandatory and required content collides in practice with other contents required. So today, after nearly ten years of legal issuing of the Law, the teachers behavior cannot be neglected, for ensuring to students the implementation of the content provided by law and by other normative documents is a fundamental contribution to a culture of human rights.